Caste, Religion and Otherness: Probing the Aporia of the Dalit–Muslim Question in Omprakash Valmiki’s Short Story ‘Salaam’ and Mohandas Naimishraya’s Autobiography Apne Apne Pinjare (Cages of Our Own) - Bairva, Mukesh Kumar (Contemporary voice of dalit, 2023)
Dalit texts generally foreground the question of marginality in the context of caste-based discrimination, exclusion and violence. Interestingly, Mohan Das Naimishraya’s Apne Apne Pinjare (Cages of Our Own) and Omprakash Valmiki’s ‘Salaam’ go beyond the scope of exploring the dialectics of dominance and resistance by probing the complexity of otherness. The appropriation of the Dalit subject by the neo-Brahmanical forces us to rethink the notion of marginality. The aversion and hatred of Dalits against Muslims and the identification of Dalits as Hindus by Muslims obfuscate the power dynamics in a communal and casteist socius. The complex Dalit–Muslim relationship re-configures the power relations underpinning untouchability and propels us to re-interpret the troubled category of the ‘Other’. This article explores the epistemological and ontological uncertainty about the marginal categories which entail the historical experience of violence, disenfranchisement and oppression. The two Dalit texts problematize the identity of the Dalit as an ‘Other’ vis-a-vis the Muslim subject and thus highlight the liminality of the subaltern subject. This article seeks to decode the aporia of Dalit–Muslim question in the casteist and communally fractured social order.